Body-mass index and cancer mortality in the Asia-Pacific Cohort Studies Collaboration: Pooled analyses of 424 519 participants - Parr, C.; Batty, G.; Lam, T.; Barzi, F.; Fang, X.; Ho, S.; Jee, S.; Ansary-Moghaddam, A.; Jamrozik, K.; Ueshima, H.; Woodward, M.; Huxley, Rachel (The Lancet Publishing Group, 2010)
Background: Excess bodyweight is an established risk factor for several types of cancer, but there are sparse data from Asian populations, where the proportion of overweight and obese individuals is increasing rapidly and adiposity can be substantially greater for the same body-mass index (BMI) compared with people from Western populations. Methods: We examined associations of adult BMI with cancer mortality (overall and for 20 cancer sites) in geographic populations from Asia and from Australia and New Zealand (ANZ), within the Asia-Pacific Cohort Studies Collaboration, by use of Cox regression analysis. Pooled data from 39 cohorts (recruitment 1961-99, median follow-up 4 years) were analysed for 424 519 participants (77% Asian; 41% female; mean recruitment age 48 years) with individual data on BMI. Findings: After excluding those with follow-up of less than 3 years, 4872 cancer deaths occurred in 401 215 participants. Hazard ratios for cancer sites with increased mortality risk in obese (BMI =30 kg/m2) compared with normal weight participants (BMI 18·5-24·9 kg/m2) were: 1·21 (95% CI 1·09-1·36) for all-cause cancer (excluding lung and upper aerodigestive tract), 1·50 (1·13-1·99) for colon, 1·68 (1·06-2·67) for rectum, 1·63 (1·13-2·35) for breast in women 60 years or older, 2·62 (1·57-4·37) for ovary, 4·21 (1·89-9·39) for cervix, 1·45 (0·97-2·19) for prostate, and 1·66 (1·03-2·68) for leukaemia (all after left censoring at 3 years). The increased risk associated with a 5-unit increase in BMI for those with BMI of 18·5 kg/m2 or higher was 1·09 (95% CI 1·04-1·14) for all cancers (excluding lung and upper aerodigestive tract). There was little evidence of regional differences in relative risk of cancer with higher BMI, apart from cancers of the oropharynx and larynx, where the association was inverse in ANZ and absent in Asia. Interpretation: Overweight and obese individuals in populations across the Asia-Pacific region have a significantly increased risk of mortality from cancer. Strategies to prevent individuals from becoming overweight and obese in Asia are needed to reduce the burden of cancer that is expected if the obesity epidemic continues. Funding: National Health and Medical Research Council of Australia, Health Research Council of New Zealand, and Pfizer Inc. © 2010 Elsevier Ltd.